Weight management practices of Australian Olympic combat sport athletes - Reale, R.; Slater, G.; Burke, L. M. (International Journal of Sports Physiology and Performance, 2018)
Combat sport athletes undertake chronic and rapid weight loss (RWL) practices to qualify for weight divisions lower than their training weight. Variation between sports in the prevalence, methods, and magnitude of weight loss as well as recovery practices may be influenced by factors including competition level and culture. Differences in methodologies of previous research in combat sports make direct comparisons difficult; thus, this study aimed to examine weight loss practices among all Olympic combat sports in Australia, using standardized methodology. Methods: High-caliber competitors in wrestling, boxing, judo, and taekwondo (n=260) at Australian competitions were surveyed using a validated tool that provides quantification of how extreme an athlete's weight loss practices are: the rapid weight loss score (RWLS). Additional qualitative and quantitative survey data were also collected. Results: Neither sport, sex, nor weight division group had an effect on RWLS; however, a significant effect of athlete caliber was detected (F2,215 = 4.953, mean square error=4.757, P=.00792). Differences between sports were also evident for most weight ever lost in order to compete (H 19.92, P.0002), age at which weight cutting began (H=16.34, P=.001), and selected methods/patterns of RWL (P<.001). Weight cycling between competitions was common among all sports as were influences on athlete's behaviors. Conclusions: Although many similarities in weight loss practices and experiences exist between combat sports, specific differences were evident. Nuanced, context/culturally specific guidelines should be devised to assist fighters' in optimizing performance while minimizing health implications.